2017
DOI: 10.1186/s12891-017-1492-6
|View full text |Cite
|
Sign up to set email alerts
|

Allograft tendon reconstruction of the anterior talofibular ligament and calcaneofibular Ligament in the treatment of chronic ankle instability

Abstract: BackgroundThe purpose was retrospectively to investigate functional and clinical outcomes after anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) reconstruction using a single allograft.MethodsPatients with severe chronic lateral instability of the ankle underwent surgery after conservative treatment failed. Ultrasounds of the ankle were performed, and if the AFTL and CFL were completely torn without enough soft tissue for repair, the ligaments were reconstructed using allograft tendon. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 22 publications
0
45
0
2
Order By: Relevance
“…Surgery is recommended in patients with chronic lateral ankle instability resistant to conservative methods, so as to restore stability, prevent intra-articular derangement and avoid early osteoarthritis [1,8,9,15,17]. The Broström technique, possibly associated with the Gould modification, is the gold standard of all proposed surgical repair techniques for chronic lateral ankle instability [1,12,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is recommended in patients with chronic lateral ankle instability resistant to conservative methods, so as to restore stability, prevent intra-articular derangement and avoid early osteoarthritis [1,8,9,15,17]. The Broström technique, possibly associated with the Gould modification, is the gold standard of all proposed surgical repair techniques for chronic lateral ankle instability [1,12,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical repairs and reconstructions aim to restore as close as possible the normal anatomy. In non-anatomical reconstructions, autografts or allografts are used: the normal biomechanics of the ankle may be slightly altered in favour of greater stability [12,[16][17][18]. Recently, arthroscopic and combined arthroscopic-percutaneous approaches have been developed [2,[19][20][21][22].…”
mentioning
confidence: 99%
“…eReferences 2, 3, 7, 8, 12, 26 29, 35, 36, 38, 42 44, 46, 69, 73, 74, 86, 90, 93, 95, 97, 102, 103, 105, 107, 114, 117 119, 132, 134, 139, 142, 151, 153, 156, 157, 166, 179, 180, 184, 189, 191, 196, 197, 199, 206, 215, 216, 226, 229, 234.…”
mentioning
confidence: 99%
“…gReferences 9, 15, 33, 35, 56, 57, 69, 80, 85, 94, 95, 119, 133, 137, 139, 148, 171, 179, 184, 186, 189, 191, 206, 216, 229.…”
mentioning
confidence: 99%
“…Dong et al reported the surgical effects of 20 cases receiving remnant-preserving lateral ankle ligament reconstruction, and suggested that, the ATFL-preserving remnant better recovered the function after ankle ligament reconstruction, and emphasized the importance of remnant-preserving surgery and favorable clinical follow-up results [28]. However, Wang et al performed ATFL reconstruction to treat 19 CLAI cases, no ATFL ligament remnant was preserved introperatively, and patients were followed up for an average of 30 months after surgery; their results suggested that, the AOFAS score was improved from 64.00 to 90.32 points, and the authors indicated that remnant-preservation was unnecessary in ATFL reconstruction [29]. Jiang et al…”
Section: Discussionmentioning
confidence: 99%